Moderating Effect of Cyber Bullying on the Psychological Well-Being of In-School Adolescents in Benin Edo State Nigeria - Okoiye, O., Emmanuel; Anayochi .N, Nwoga; Onah, A., Thompson (European Journal of Sustainable Development, 2015)
This study adopted a descriptive survey research design of ex-post factor type to determine the moderating effect of cyber bullying on the psychological well-being of in-school adolescents in Benin Edo State Nigeria. Simple random sampling technique was used to select 300 in-school adolescents from fifteen randomly selected secondary schools in Benin Edo state. Four instruments used were: Cyber Bullying Prevalence Questionnaire (CBPQ) (?= 0.84); Rosenberg's self-esteem scale (RSE) (?= 0.88); Self-Concept Clarity Scale: (?= 0.88) and General Self-Efficacy (GSE) scale (?= 0.90). Two research questions were answered and three hypotheses tested at 0.05 level of significance. Data were analysed using Pearson Product Moment Correlation and Multiple Regression. The measures of association between the variables identified in the study revealed that there was significant relationship between the variables (self-esteem, self-concept, self-efficacy and cyber bullying). The study produced an F-Ratio (3/296) = 10.451which implies that the consequence of cyber bullying has impact on in-school adolescent’s self-esteem, self-concept and self-efficacy. Also, self-esteem correlate with cyber bullying of-in school adolescents, r (298) = .289, p< .05. Likewise, self-concept correlates significantly with cyber bullying of in-school adolescents, r (298) = .457, p< .05. Furthermore, self-efficacy correlate significantly with cyber bullying of in-school adolescents, r (298) = .261, p< .05. Therefore, it is recommended that adolescents should be taught moral instructions in school as it would help them be of good character and develop the ability to negotiate relationships positively with significant other in the society. Keywords: Adolescent, Cyber Bullying, Self-esteem, Self-concept, Self-efficacy, Benin and Nigeria.